Intertwined gender inequality in Desy Anwar's "Growing Pains" - Zulfie, Vivian; Kusumayanti, Dina Dyah (LITERA, 2023)
Rooted within structures of patriarchy and modern life, gender equality seems still far from achieved. Providing social issues like gender inequality, literary works become reliable proof to portray subordination or discrimination against women. Thus, this study aspires to strive for women empowerment and re-educating men expectantly to tackle the problems of gender inequality. Desy Anwar's Growing Pains is interlaced with gender issues in five chapters. This research aims to unveil a range of gender conflicts and the efforts of the female main characters to overcome the hardships in life. Descriptive criticism is employed as a method of analysis. Following Lazar's Feminist Critical Discourse Analysis (2014), the linguistic data in the form of lexical choices, phrases, and clauses are first identified based on the language features indicating gender inequality or violence. Eckert and McConnell-Ginet's language theory (2013) is applied in unraveling the details of linguistic evidence. Then, interpreting the discursive logic is correlated with the cultural realm of the novel Hence, the findings yield that all the selected lexicons, phrases, and clauses of the novel construct the meanings of gender issues. Socio-cultural experiences represent forms of gender-based violence such as asymmetrical family systems, misogynistic practices, gender-identity threatening, deviant female promiscuity, and cruel motherhood portrayal. The symbolic and psychological impacts are also identified, referring to post-patriarchal regimes. Although there seems to be effortful survival in masculine domination, both internal and external factors are in support of constructed gender inequalities. Eventually, all the female characters are demonstrated as the vulnerably subordinated subjects of neoliberal hegemony. This research fervently aims to recall the awareness of symbolic gender violence due to ongoing powers that halt the emergence of gender equality and reshape it into hegemonic strategies.Keywords: hegemony, inequality, misogyny, patriarchy, symbolic violence